Voices on Italy’s Recent History: Aulò: Roma postcoloniale and La quarta via - Luijnenburg, Linde (Incontri. Rivista europea di studi italiani, 2013)
Recensione di: Simone Brioni (ed.), Somalitalia: Quattro Vie per Mogadiscio/Somalitalia: Four Roads to Mogadishu. With the documentary La quarta via: Mogadiscio, Pavia. Roma, Kimerafilm,2012, 37 p., ISBN: 9788890771408. € 15,00. Ribka Sibhatu, Aulò! Aulò! Aulò! Poesie di nostalgia, d’esilio ed’amore. Aulò! Aulò! Aulò! Poems of Nostalgia, Exile and Love.With the documentary by Simone Brioni (ed.) Aulò: Romapostcoloniale, Roma, Kimerafilm, 2012, 41 p., ISBN:9788890771415. € 15,00.